The Vitamin D and its impact on musculoskeletal system and endurance among athletes – a narrative review of literature - Grzymek, Magdalena; Kadłuczka, Joanna; Hejduk, Makary; Papuga, Aleksandra; Pawłucka, Aleksandra; Kraska, Katarzyna; Pawłucka, Katarzyna; Bury, Justyna; Potoniec, Jan; Sobek, Aneta; et al. (Quality in Sport, 2026)
Background. Vitamin D is known as a crucial molecule in bone metabolism and optimal bone forming process. Naturally is activated by sun radiation in skin and then hydrolysed in the liver and kidneys. The risk of deficient or insufficient level of the active metabolite is depended on geographic altitude, skin colour and inadequate supplementation. The athlete’s population are prone to lower level of this vitamin. Traditionally has been recognized for its role in calcium homeostasis and bone metabolism; however, increasing evidence indicates that it also plays a crucial role in skeletal muscle function. Skeletal muscle is now considered an important target tissue for vitamin D action due to the presence of vitamin D receptors (VDRs) within muscle fibers. Through genomic and non-genomic mechanisms, vitamin D influences muscle development, contractility, regeneration, and overall physical performance. Consequently, adequate vitamin D status is essential not only for maintaining skeletal integrity but also for optimizing muscle function and preventing musculoskeletal disorders.